An approach for speed limit determination for vehicle tracking in case of GID ambiguity and lack of information in navigation maps. Issue 3 (4th September 2017) - Haliti, Nusret; Kadriu, Arbana; Jusufi, Mensur
Abstract : Purpose: The purpose of the research presented in this paper is about an algorithm used for speed limit determination, in cases when there is ambiguity in determining the correct road data for a tracked vehicle. This algorithm resolves the glitch that happens when emitted global positioning system (GPS) data are ambiguous regarding roads that are very near to each other. Furthermore, we give a solution for other difficulties regarding the speed limit involving accuracy of emitted data and lack of information in navigation maps. Design/methodology/approach: Our vehicle tracking system parses all GPS data from different vehicles to a single centralized database. It uses balancers and parsers to parse these data. Balancers use algorithms like round-robin to choose between different parsers. Information gained by the GPS unit is parsed, and then sent to a central server at regular intervals. For the gained data, we try to analyze the speed limit problem when tracking vehicles, analyze the challenges that are linked with speed limit problem, define a solution for the above discussed drawbacks and measure the driving performance. Findings: We have already developed a fully functioning tracking system, which uses the above-described algorithm in tracking of few hundred vehicles, which makes approximately 1, 300, 000 requests per day, resulting in more than 4, 000, 000 tracking records gained in six months. The system monitors the motion of different vehicles using the gained GPS data from the first hand. This monitoring is done by developing web and mobile applications for third-party actors. This monitoring regards not only to the raw-produced data but also to new metrics that are derived from the raw one. Originality/value: To our knowledge, there is not a similar algorithm/technology that can be of help in case of geographical identifier (GID) ambiguity. This research presents a solution to a real problem that we faced and which could not be answered by any of the current algorithms and technologies regarding the speed limit. Therefore, we consider this paper as highly original, which brings value in the field of pervasive computing and machine-to-machine communication.